Cryogenic pipe flow simulation for liquid nitrogen under steady state conditions - Lim, Chong Lye (2019)
Cryogenics, a thermodynamics study on fluids at temperatures less than 120 K, has many applications in a variety of fields. However, the problem of the high temperature difference between ambient air and temperature of the cryogenic liquid in the transfer line, is a limiting factor. Thus, temperature leakage for heat gain in the transfer line is of utmost concern. Experimental works can be rather costly and dedicated Computational Fluid Dynamics (CFD) for cryogenics are limited and require many supporting peripherals. The aim of this study is to simulate velocity and temperature profiles of line liquid nitrogen using common CFD package (FLUENT) for fast tracking of flow characteristics of liquid nitrogen (LN2). In addition, this study numerically investigates the thermal and hydrodynamic performance of the Vacuum Insulated Pipe (VIP) and Polyurethane (PU) foam insulations by using an experimentally validated finite volume method (FVM) model. The continuum, momentum and energy equations are solved in the cryogenic temperature range. The LN2 is assumed as a homogenous liquid and incompressible at 4 bar operating pressure. The geometry and physics of the liquid nitrogen flow are axisymmetric for the horizontal transfer line. The simulation model in this study is solved using the commercially available CFD computational code. This study numerically investigates single phase heat transfer of LN2 pipe flow for the inlet volume flow range of 250 to 2000 litre per hour (LPH) at 4 bar operating pressure and 300 K ambient temperature under steady state conditions. A three-dimensional LN2 pipe flow with k-epsilon (k-ε) turbulence simulation model has been conducted using CFD ANSYS FLUENT. Both insulator and jacket pipe layers are created as shell layers where the shell conduction model predicts the thermal resistance incurred in the presence of multilayers. The axisymmetric velocity results from the investigation are within the range of 0.44 to 3.39 m/s for inlet volume flow rates of 250 to 2000 LPH. The temperature distributions resulting from the LN2 pipe flow simulation with VIP are within the range of 77.0 K to 82.1 K for inlet volume flow rates of 250 to 2000 LPH. The wall heat flux for VIP used for the present study shows the relatively high heat transfer at the wall as compared to PU foam. In conclusion, the simulation model of LN2 pipe flow successfully developed and shown an optimum combination of multilayer insulation (MLI) with 20 layers and high vacuum provides the wall heat flux less than 1 W/m2. The simulation results provide useful insights on the flow field of the cryogenic transfer line.